Amplification of trpEG: adaptation of Buchnera aphidicola to an endosymbiotic association with aphids. - Lai, C Y (1994)
Survival of aphids is dependent on an association with a prokaryotic endosymbiont (Buchnera aphidicola) found in specialized cells within the aphid body cavity. Recent nutritional and physiological studies have indicated that one of the functions of the endosymbionts is the synthesis of tryptophan [Douglas, A. E. & Prosser, W. A. (1992) J. Insect Physiol. 38, 565-568]. B. aphidicola resembles in many of its properties free-living prokaryotes. An adaptation to an endosymbiosis involving the overproduction of tryptophan would necessitate alterations that modify the effect of regulatory systems that in free-living organisms function to reduce enzyme activity under conditions of excess tryptophan. We have cloned and sequenced the genes for B. aphidicola trpEG encoding anthranilate synthase, the first enzyme of the tryptophan biosynthetic pathway, which in free-living bacteria is feedback-inhibited by tryptophan. Amino acid sequence comparisons indicate that the B. aphidicola enzyme has all of the key residues involved in allosteric feedback inhibition. Evidence is presented indicating that trpEG is present as four tandem repeats on a circular plasmid. Relative to B. aphidicola trpDC(F)BA (the chromosomal genes coding for the remaining enzymes of the tryptophan biosynthetic pathway) trpEG is amplified 14- to 15-fold. These findings suggest that the effect of inhibition by accumulated tryptophan may be overcome by overproduction of anthranilate synthase. Our results demonstrate the acquisition of a new property (gene amplification) as an adaptation to an endosymbiotic association in which B. aphidicola overproduces tryptophan for the aphid host.